ENHANCEMENT OF CURCUMIN SOLUBILITY AND DISSOLUTION BY ADSORPTION IN MESOPOROUS SBA-15 - FITRIANI, LILI; AZIZAH, HUSNUN; HASANAH, USWATUL; ZAINI, ERIZAL (International Journal of Applied Pharmaceutics, 2023)
Objective: Curcumin belongs to BCS class IV, which has low solubility, around 7.8 µg/ml and its results of low bioavailability. The study aimed to enhance solubility and dissolution rate of curcumin by adsorption in mesoporous silica SBA-15. Methods: The synthesis of SBA-15 was done by using tetraethyl orthosilicate (TEOS) as silica precursors and Pluronic P123 (EO20PO70EO20) as template of pore-forming. Impregnation of curcumin in SBA-15 was conducted by evaporation in ethanol solution with 2:1 of curcumin: SBA-15 proportion. Curcumin-SBA-15 were characterized by Nitrogen Adsorption-Desorption Isotherm, Powder X-Ray Diffraction (PXRD), Fourier Transformed Infrared (FT-IR), Differential Scanning Calorimetry (DSC), and Scanning Electron Microscopy (SEM). The solubility test was performed by using an orbital shaker for 24 h in CO2-free distilled water. The dissolution rate was conducted in CO2-free distilled water using USP Type-II dissolution test apparatus. Results: Efficiency entrapment of curcumin-SBA-15 was 59.433%. The successful adsorption of curcumin in SBA-15 was confirmed by reducing its surface area (48.165 m2/g) and pore volume (0.073x10-1 cm3/g). The results of PXRD analysis showed that decreased in the intensity of the diffraction peak. In addition, the FTIR spectrum of curcumin-SBA-15 was similar to its intact component. The solubility and dissolution rate test of curcumin-SBA-15 enhanced 2.201 times and 3.214 times at 60 min compared to intact curcumin. Conclusion: It can be concluded that the adsorption of curcumin in SBA-15 increased both the solubility and dissolution rate of curcumin.